2022
DOI: 10.14744/eej.2022.85047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GuttaClear on postoperative pain after root canal retreatment: a randomized clinical trial

Abstract: Objective The aim of this study was to evaluate postoperative pain after non-surgical root canal retreatment with or without GuttaClear. Methods Sixty participants were randomly distributed in this non-inferiority trial into two parallel single-blinded experimental groups (Group1: non-solvent, Group2: solvent). After root canal retreatment, the participants completed questionnaires using direct (numerical rating scales) and indirect (number of analgesics taken) measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…From the electronic databases and manual search, a total of 596 articles were obtained. Fourteen studies were shortlisted for full-text screening, and finally, two randomized controlled trials[ 11 , 12 ] were identified to undergo quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the electronic databases and manual search, a total of 596 articles were obtained. Fourteen studies were shortlisted for full-text screening, and finally, two randomized controlled trials[ 11 , 12 ] were identified to undergo quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sirijindamai D et al . [ 12 ] conducted a unique study that stands out as the only one to include immediate postoperative pain assessment alongside five other time points. In contrast, Topçuoğlu and Topçuoğlu[ 19 ] reported that the highest pain levels at all time points occurred 6 h after treatment, which differs from the present study’s findings indicating the highest pain immediately after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations